Fourier Inversion Formulas for Multiple-Asset Option Pricing - Bruno Feunou; Ernest Tafolong (Bank of Canada, 2015)
Plain vanilla options have a single underlying asset and a single condition on the payoff at the expiration date. For this class of options, a well-known result of Duffie, Pan and Singleton (2000) shows how to invert the characteristic function to obtain a closed-form formula for their prices. However, multiple-asset and multiple-condition derivatives such as rainbow options cannot be priced within this framework. Utilizing inversion of the Fourier transform - and resorting to neither the Black-Scholes framework nor the affine models settings - the authors provide an analytical solution for options whose payoffs depend on two or more conditions. Numerical experiments based on the multiple-asset and multiple-condition derivatives are provided to illustrate the usefulness of the proposed approach.
Keywords: G12; 330; Asset pricing